Generalized resistance to pruritogen-induced scratching in the C3H/HeJ strain - Zhang, Yanbin; Richter, Nicole; König, Christine; Kremer, Andreas E.; Zimmermann, Katharina (Frontiers in Molecular Neuroscience, 2022)
Previously the effect of the pruritogens histamine and chloroquine were tested in eleven inbred mouse strains and, this study identified resistant and sensitive strains, consistent with the observation that itch underlies large variability in human populations. In the present study we used the low responder C3H/HeJ (C3H) and the more sensitive C57BL/6J (C57) strain to find out if resistance and sensitivity to develop pruritus is restricted to histamine and chloroquine or extends to other known pruritogens. We tested five additional commonly known pruritogens. We established dose-response relationships by injecting four concentrations of the pruritogens in the range of 0.3, 1, 3 and 10-fold in the nuchal fold. Then we assessed scratching behaviour for 30 minutes after injection with an automated custom-designed device based on the bilateral implantation of mini-magnets in the hind paws and on single cages placed within a magnetic coil. We found that resistance to pruritogens is a general phenotype of the C3H strain and extends to all pruritogens tested, including not only histamine and chloroquine, but also endothelin, trypsin, 5-HT (serotonin), the short peptide SLIGRL and Lysophosphatidic acid. C57 were more sensitive to all pruritogens and, in contrast to C3H, dose-response relationships were evident for some of the pruritogens. In general, comparable peak scratch responses were observed for the 0.3-fold concentrations of the pruritogens in C57 whereas C3H required at least the 10-fold concentration and still displayed only between 5-33 % of the scratch responses observed in C57 for the respective pruritogen. The general resistance to pruritogens and the low level of scratching behaviour found in the C3H strain is an interesting trait and represents a model for the study of heritability of itch. It is accompanied in C3H with a higher sensitivity in assays of nociception.